The effectiveness of mitomycin C in Otolaryngology procedures: A systematic review. (29th October 2021) - Luu, Kimberly; Tellez, Paula A.; Chadha, Neil K.
Abstract: Objective: Many studies have evaluated the effectiveness of topical intraoperative mitomycin (MCC) usage in a wide range of otolaryngologic procedures with variable conclusions on effectiveness. This systematic review aims to provide a qualitative estimation of mitomycin C's treatment effectiveness in maintaining or preventing stenosis after surgical interventions. Design and Setting: Following the PRISMA guideline, a comprehensive systematic search of MEDLINE, EMBASE and CINAHL databases was performed including hand‐searching and cross‐reference checking. Participants: The search was limited to humans, sample size greater than two and study designs including a comparative arm. Main Outcome Measures: Outcome measures varied but included rates of restenosis, number of procedures, and post‐surgical patency. Results: A total of 571 unique abstracts and 109 full articles were reviewed. Seventy‐seven studies were included in the final analysis. The available evidence ranged from case series to randomized control studies. Meta‐analysis was deemed inappropriate due to heterogeneity of study design. Thirty‐eight studies assessed the effective of MCC in dacryocystorhinostomy, which is reported in a separate meta‐analysis. All other studies were categorized into otolaryngologic site and pathology including choanal atresia ( n = 5), endoscopic sinus surgery ( n = 12), airway procedures ( n = 9), esophageal procedures ( n = 8) and other ( n = 2). Conclusions: The published literature on the effectiveness of MMC was mixed, but suggested topical MMC improved surgical outcomes in many otolaryngologic procedures compared to controls. This was the first review to assemble literature on MMC usage for different surgical procedures. Comprehensive interpretation of the data was limited due to heterogeneity in primary outcome, procedure type and study quality. High‐quality prospective and randomized controlled studies are required to further confirm the positive effect of MMC use on surgical outcomes.